Teacher’s Efforts to Improve the Moral Development of Vocational School Students - Affifah Novianingsih; Agus Efendi; Wiji Khurniawati (Journal of Informatics and Vocational Education, 2024)
There is no denying that teens' morals are impacted by globalization. This phenomena highlights the need for moral education, particularly at the vocational school level, where students will eventually enter the workforce. As such, moral education is extremely important because it focuses on improving character and ethics in addition to competency development. The role of instructors becomes crucial in promoting ethics, morals, and character. This study aims to describe teacher's efforts to increase the moral development of students at the vocational school level and impact its implementation. Data collection techniques use observation and interviews. The research method uses descriptive qualitative. Participants were chosen with the technique of purposive sampling. Data analysis using data reduction, data presentation, conclusions, and verification. Research results show teachers’ efforts to increase the moral development of students at the vocational school level are carried out during learning to become exemplary, instill Pancasila values, habituation culture work, push learning peers, and gift constructive feedback proven own impact positive to the moral development of students with indication that students showing moral values according to Thomas Lickona. This research gives the line bottom importance of teachers' efforts to improve participant morale in vocational high school education as preparation for facing current globalization and the demands of the world of work.Keywords: Moral Development, Students, Teacher Efforts, Vocational School Students